The handbook of biomarkers - Jain, K. K. (Humana Press, 2017)
Involved in nearly every therapeutic area, particularly cancer, biomarkers have experienced tremendous advances since the first edition of this book, both in the discovery of biomarkers and in their applications. To aid in this imperative research, Prof. Kewal K. Jain's Handbook of Biomarkers, Second Edition features a full revision and additional chapters to thoroughly describe many different types of biomarkers and their discovery using various "--Omics" technologies, along with the background information needed for the evaluation of biomarkers as well as the essential procedures for their validation and use in clinical trials. With biomarkers described first according to technologies and then according to various diseases, this detailed book features the key correlations between diseases and classifications of biomarkers, which provides the reader with a guide to sort out current and future biomarkers. Comprehensive and cutting-edge, The Handbook of Biomarkers, Second Edition serves as a vital guide to furthering our understanding of biomarkers, which, by facilitating the combination of therapeutics with diagnostics, promise to play an important role in the development of personalized medicine, one of the most important trends in healthcare today.- Resumé vydavatel
Includes index.
Keywords: biologické markery; biological markers; elektronické knihy; příručky; electronic books; handbooks and manuals